Pre-, During-, and Post-COVID-19: Students’ Evaluations of Instructor Preparation and Course Delivery - Nandasena, N. A. K.; Hefny, Ashraf (Journal of Engineering Education Transformations, 2025)
The spread of SARS-CoV-2 (COVID-19) affected the global education system. Traditional face-to-face learning was disturbed while online learning was employed to continue education without interruption during the pandemic. Instructors and students faced unexpected challenges in preparation for their routines, and course preparation and delivery, class attendance, and knowledge receipt were influenced by their attitudes, experience, and adaptation to the new setting. The purpose of this study was to investigate how students embraced changes in course modification and instructor preparation from the pre- to post-COVID period; 212 undergraduates and 24 postgraduates enrolled in engineering courses were given a multiple-choice questionnaire including an open-ended feedback form. The questionnaire included instructor-wise and course-wise parameters measuring the instructor’s interest/dedication, effectiveness, encouragement, assessment quality, and delivery of course material, and the overall organization, knowledge, and quality of the course. Despite limitations of the study, the students rated the instructor and course as having higher quality during the post-COVID period than before the pandemic, suggesting that the effective use of both face-to-face and online techniques created a better learning environment. The undergraduate students observed the continuous development of the instructor and course in the transition period; however, only online learning during the pandemic produced low satisfaction among the postgraduate students.